Management of stem borer (Chilo partellus Swinhoe) in maize using conventional pesticides in Chitwan, Nepal (Journal of Maize Research and Development, 2016)
The stem borer (Chilo partellus Swinhoe) is one of the most destructive pests of maize crop. Research experimentations were carried out on maize to control stem borer using conventional pesticides under field condition during summer season of two consecutive years from 2015 to 2016 at Rampur, Chitwan. All used pesticides had significant effect (P≤0.05) on percent damage and crop yield over control. In 2015, the lower percent damage (5.3%) with higher crop yield (4.52 t ha-1) and lowest insect score (1.00) was observed in plot sprayed with spinosad 45% EC at 0.5 ml L-1 of water followed by plot treated with chloropyriphos 50% EC+cypermethrin 5% EC @1.5ml L-1 of water with percent damage of 6.60%, crop yield (4.23 t ha-1) and insect score of 1.60. Almost similar trend of insect incidence along with damage percentage and yield data were observed in 2016. The higher percent damage control (79.06%) was observed at the plot sprayed after spinosad 45% EC at 0.5 ml L-1 of water with higher crop yield (4.58 t ha-1) and lowest insect score (1.00) followed by the plot treated with imidacloprid 17.8% @ 0.5 ml L-1 of water with percent damage control of 73.10 %, crop yield (3.38 t/ha) and insect sore 1.50. The highest percent damage (20.63%) was observed in the control plot with lower yield (0.95 t ha-1) and highest insect score (6.00). Over the years, spinosad 45% EC at 0.5 ml L-1 of water was effective bio-pesticide to control maize stem borer damage and also increase the yield.